Kolaborasi Pemerintah dalam Menekan Angka Balap Liar di Kota Pekanbaru - Salsa Sabilla Putri; Khairul Amri (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
Along with population growth in Indonesia, the increase in people's need for transportation has created problems that have not been resolved in Pekanbaru City. Traffic problems, especially among teenagers, are something the government needs to pay more attention to. This research aims to determine the collaboration process that has been carried out by several stakeholders to suppress illegal racing in Pekanbaru City and identify factors that hinder the collaboration process of the Pekanbaru Police Traffic Unit, the Education Service in this case Pekanbaru 3 Public High School and the Pekanbaru City Transportation Service. This research uses Ansell and Gash's theory in Retno, Hardi & Abd (2020) which uses indicators of Face to Face Dialogue, Trust Building, Commitment to Process, Shared Understanding, Intermedite Outcome. This research uses a qualitative type of research using a phenomenological approach. The results of the research found that the collaboration carried out by the Pekanbaru Police Traffic Unit with related stakeholders in reducing the number of illegal races was quite optimal, this can be seen from the achievement of all the theoretical indicators used in this research even though there were several obstacles faced in its implementation.